Analysis of Quranic Arguments on the Abstraction of the Soul on with Emphasis on Narrative Interpretations (Exegeses) - Ṣaḥebeh Ashouri; Zohreh Borghei (آموزه‌‌های فلسفه اسلامي, 2021)
The issue of the abstraction of the soul has always been considered by Muslim thinkers and philosophers due to its fundamental role in philosophical topics such as anthropology, epistemology, teleology, etc. The question of the present study is whether the discussion of the abstraction of the soul is in line with the view of the Qur'an? This article examines the interpretations (exegeses) of the verses cited for abstraction as well as the narrations included in these verses, explaining the Qur'an’s view on abstraction by emphasizing narrative interpretations. Four categories of verses have been cited on the abstraction of the soul: First, the verses that express the creation of the Souls. The second category of verses that refer to the relationship between the Souls and God. The third category of verses refers to inner actions, especially verses that indicate its perception and levels. The fourth group of verses related to purgatory and resurrection, which state that after death and the destruction of the body, the truth of man, taken away (cause to death) by the divine angels, remains and has observations. Many narrations also confirm the abstraction of the soul. The cases in which the appearance of the narrations contradicts the abstraction of the soul can be justified and interpreted for definite and documented reasons. This article deals with this issue with a documentary-library method and with a descriptive-analytical approach.